Generating family dynamics through the design of residential care home for abandoned and neglected children in the Philippines - Ngan, Lorenzo O.; Lacson, David Xander T. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The issue of abandoned and neglected children in the Philippines has been largely
addressed through the use of long-term institutionalization in residential care homes
[RCH]. This research tackles the issue of abandoned and neglected children and their
detrimental internment in existing childcare RCHs in the Philippines. This research
thereby examines the inflexibility of existing RCHs to accommodate family and
community-based childcare. This research reveals two distinct issues, systematic failure
to adequately support struggling families to abate the abandonment of children. and the
fixation on RCHs as a commutative solution. Data on RCH user experiences, programs,
and sentiments on architectural design was gathered through informal interviews and a
literature review. Possible sites for the proposed project were identified, analyzed, and
sorted through site selection criteria to determine the best program compatibility. A
design proposal of a mixed-use RCH that is a combination of an RCH, daycare center,
and healthcare center was thereafter determined and proposed.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Abandoned children -- Philippines; Residential Care Homes for Children; Child care -- Philippines; Family day care -- Philippines